Deviation and communicative necessity: a pragmatic approach - Dr.Hayder Oudah Gatea (Journal of College of Education, 2024)
Deviation is a stylistic contextual departure that has dominated creative texts in ancient and modern times, and linguistic studies such as grammar, rhetoric, morphology, and semantics have been full of it. This celebration was the reason for its appearance in modern linguistic and communicative studies, especially since linguistics deals with creative texts as the material that should be a field for stylistic and communicative creativity, in which the creative movement of the transmitter appears. This interpenetrating application between the two studies has led to a great convergence between deviation and some topics with communicative standards, such as speech acts and communicative implicit coherence. It appeared to the research that they are a departure from the apparent composition to the implicit meanings in the environment of the text as a whole, without cutting the texts or dividing them. This convergence appeared clearly in some Qur’anic texts; Because the condition of contextual departure is linked to the creative ability of the producer to succeed in employing the criteria of departure so that the modified text becomes a new artistic image inspired by the expressive energy of the language and the creator alike, while leaving sufficient space for the recipient to navigate in the interpretation of the modified texts